2012
DOI: 10.1515/hf.2011.188
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of copper solubilization and reaction in micronized copper treated wood by electron paramagnetic resonance (EPR) spectroscopy

Abstract: The purpose of this study was to compare the reaction chemistry of micronized copper and alkaline copper treatments with wood and to determine how fast copper is solubilized during the reaction between the acidic functionality in wood and the basic copper carbonate (CuCO 3 ). Copper species produced in wood by various treatment methods were analyzed by electron paramagnetic resonance (EPR) spectroscopy. The effects of time and solution concentration on the spectral parameters of copper complexes in sawdust tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The spectra of the Cu complexes exhibited g z values of ∼2.382 and A z tensors of ∼130 G, which were typical of the Cu-wood complexes formed with only Cu-oxygen bonding (Hoffmann et al 2008). They were also similar to those of commercial MCQ-treated samples (Xue et al 2012). The Cu contents of the samples determined by XRF were plotted against the corresponding EPR intensities and a linear correlation coefficient (R 2 ) of 0.995 was found (Eq.…”
Section: Sawdust Treatment With Cuso 4 Solutionsmentioning
confidence: 81%
See 2 more Smart Citations
“…The spectra of the Cu complexes exhibited g z values of ∼2.382 and A z tensors of ∼130 G, which were typical of the Cu-wood complexes formed with only Cu-oxygen bonding (Hoffmann et al 2008). They were also similar to those of commercial MCQ-treated samples (Xue et al 2012). The Cu contents of the samples determined by XRF were plotted against the corresponding EPR intensities and a linear correlation coefficient (R 2 ) of 0.995 was found (Eq.…”
Section: Sawdust Treatment With Cuso 4 Solutionsmentioning
confidence: 81%
“…Cupric ions have been detected in the laboratory leaching of the MC quat (MCQ)-treated wood (Zhang and Ziobro 2009;Stirling and Morris 2010). A recent study (Xue et al 2012) has shown that the wood treated with an aqueous suspension of BCC produces soluble hydrated Cu species, which rapidly react with wood components resulting in Cu-wood complexes very similar to those formed by the treatment of the wood with copper sulfate (CuSO 4 ) solutions. However, the amount of the mobilized copper(II) (Cu mob ) level in the MC-treated wood has not previously been established because of the difficulty in differentiating the Cu mob from the total Cu present after treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed methodology was reported by Xue et al (2012Xue et al ( , 2013. A series of sawdust samples treated with CuSO 4 solutions at 16 different concentrations was analyzed by EPR.…”
Section: Methodsmentioning
confidence: 99%
“…However, electron paramagnetic resonance (EPR) spectroscopy is able to perform this task because BCC is antiferromagnetic and EPR silent. Earlier studies (Xue et al 2010(Xue et al , 2012 confirmed that hydrated Cu species were produced and fixed rapidly with wood upon treatment with an aqueous suspension of BCC. A quantification method based on EPR in combination with X-ray fluorescence (XRF) spectroscopy was developed for determining the reacted Cu concentrations in the treated wood (Xue et al 2013).…”
Section: Introductionmentioning
confidence: 94%